First record of non-indigenous Paracaprella pusilla Mayer, 1890 (Crustacea: Amphipoda: Caprellidae) in Golfo de Nicoya, Pacific Coast of Costa Rica - Alfaro-Montoya, Jorge (2018)
The caprellid Paracaprella pusilla from the Western Atlantic Ocean is reported for the first time in Golfo de Nicoya, Pacific coast of Costa Rica, representing the third registered invasion of this species in the Eastern Tropical Pacific (ETP), after Panama and Mexico. Individuals of P. pusilla at all stages of development, including juveniles, females (non ovigerous and ovigerous) and males, were sampled from submerged artificial structures at five locations along the coastal waters of Golfo de Nicoya between September 2014 and September 2017. This new report for the ETP indicates that the amphipod is well established in a tropical estuary of Costa Rica: Golfo de Nicoya, and represents the first caprellid reported from littoral waters of this country